Apoptotic potential of geranyl acetate in HepG2 liver cancer cells - Ahmad, Ishfaq; Maqbool, Tahir; Naz, Sadia; Inamullah; Hadi, Faheem; Atif, Muhammad (International Journal of Applied and Experimental Biology, 2023)
Natural compounds having apoptotic effects are a new potential source for anti-cancer drugs. Numerous plant phytochemicals have proven anti-cancer properties by inducing programmed cell death (apoptosis). The disease known as cancer is characterized by the uncontrollable growth of some body cells and their spread to other body regions. Worldwide, cancer is a major cause of death. The objective of the current study was to assess apoptotic potential of geranyl acetate on HepG2 cancer cell line. Cell death and cell viability in groups were assessed using the MTT, trypan blue and crystal violet to assess anti-proliferative effect. P53 ELISA was carried out to assess apoptosis. When HepG2 cells were exposed to geranyl acetate they exhibited increased cytotoxicity, decreased viability, proliferation, and increased apoptosis. It is concluded that geranyl acetate has the potential to cause apoptosis via P53 in HepG2 cells. It can also prevent cancer cell growth and proliferation.